Irradiation strongly reduces tumorigenesis of human induced pluripotent stem cells. (3rd March 2017) - Inui, Shoki; Minami, Kazumasa; Ito, Emiko; Imaizumi, Hiromasa; Mori, Seiji; Koizumi, Masahiko; Fukushima, Satsuki; Miyagawa, Shigeru; Sawa, Yoshiki; Matsuura, Nariaki
Abstract: Induced pluripotent stem (iPS) cells have demonstrated they can undergo self-renewal, attain pluripotency, and differentiate into various types of functional cells. In clinical transplantation of iPS cells, however, a major problem is the prevention of tumorigenesis. We speculated that tumor formation could be inhibited by means of irradiation. Since the main purpose of this study was to explore the prevention of tumor formation in human iPS (hiPS) cells, we tested the effects of irradiation on tumor-associated factors such as radiosensitivity, pluripotency and cell death in hiPS cells. The irradiated hiPS cells showed much higher radiosensitivity, because the survival fraction of hiPS cells irradiated with 2 Gy was < 10%, and there was no change of pluripotency. Irradiation with 2 and 4 Gy caused substantial cell death, which was mostly the result of apoptosis. Irradiation with 2 Gy was detrimental enough to cause loss of proliferation capability and trigger substantial cell death in vitro . The hiPS cells irradiated with 2 Gy were injected into NOG mice (NOD/Shi-scid, IL-2 Rγnull) for the analysis of tumor formation. The group of mice into which hiPS cells irradiated with 2 Gy was transplanted showed significant suppression of tumor formation in comparison with that of the group into which non-irradiated hiPS cells were transplanted. It can be presumed that this diminished rate of tumor formation was due to loss of proliferation and cell death caused by irradiation. Our findings suggest that tumor formation following cell therapy or organ transplantation induced by hiPS cells may be prevented by irradiation.